(untitled) (General Practice, 2023)
Introduction. The coronavirus pandemic began in 2019 and since then a huge number of people have been infected worldwide. The infection symptoms are widely defined and yet the panel of laboratory abnormalities found in infected patients is missing. Objective. We aimed to describe the clinical and laboratory features of the COVID-19 patients in Belgrade (Serbia) and the influence of socio-demographic features of the participants on vaccination status. Method. The research was performed as a cross-sectional study from October to November 2021. The included patients were the ones who visited the COVID outpatient clinic of the Primary Healthcare Center (PHC) and tested positive for Sars-CoV-2 virus infection. The data were gathered by reviewing retrospectively the patients` health charts. The data were analyzed by descriptive statistics, Pearson`s χ2 test, and we used the SPSS 20. Results. The research included 207 Sars-CoV-2 positive patients, of whom 56% were of the female sex and the majority of the participants were in the 51–60 age group (22.7%). There were 42% of the vaccinated participants. The most common symptoms the participants complained of were: fever (82.1%), cough (49.8%), malaise (32.9%), stuffed nose (29.5%), throat pain (17.9%), headache (12.1%), body pains (11.1%), loss of smell and taste (8.2%), diarrhea (2.4%). Pneumonia was found in 17.4% of the participants and high CRP values in 29%. Conclusion. The most common clinical features of the COVID-19 patients in Belgrade (Serbia) were fever, cough, and malaise. Pneumonia was found in 17.4% of the patients. The majority of the patients had normal lab work but 29% had elevated CRP. There were 42% of vaccinated patients with either of the four available vaccines and 52.9% were without comorbidities.